PHYSICAL PROPERTIES OF ROCKS OF DEEP BASINS - Gordienko V.V. (My University, 2001)
Variations of physical properties of rocks of a thick sedimentary layer are analysed as functions of the lithogenesis temperature. The maximum depth of the sedimentary basin was establish as a thermal flow function. Dependence of density, seismic wave velocity, specific electrical resistance and radiogenic heat generation of sedimentary rocks on lithogenesis were calculated. Examples of gravity models are presented for some sedimentary basins.